ANALISIS JERAMI PADI UNTUK PEMBUATAN MIKROMEMBRAN SEBAGAI PENDAUR AIR LIMBAH RUMAH TANGGA - Febriyana, Nur Aini; Mirfada, Zakiyatul; Jamila, Nurul; Wijayanto, Ach. Afif; Pradana, Novan (Program Kreativitas Mahasiswa - Penelitian, 2014)
The increase of population in Indonesia led to increased domestic waste. In addition, agricultural waste in Indonesia is very potential, such as rice straw. Rice straw ash contains silica which reached 94.5% silica is the main content of the base material micromembrane to absorb pollutants. Membrane separation is a medium that is selectively permeable to withstand certain components and skip the other components. Experimental procedures in this study includes the synthesis of silica, the manufacture of the membrane, and the membrane analysis. The results showed that the pore size of the membrane meets the standards mikromembran size from 0.3 to 10 lm. Rice straw silica functional groups located at the wave number of 3503.45 cm-1. Silica clusters seen at the peak of 1097.42 cm-1, which showed a group siloksa Si-O-Si. Optimal mass of silica used for the manufacture of silica membrane is 5 grams. The silica membrane was tested lowering the pH value from 7.2 to 6.9 caused a lot of impurities are retained and bind to the membrane. Micromembrane also lower turbidity values with 92% rejection and filter bacteria from 66000 into a 5500 colony.Â Keywords: Â straw, waste, membrane